Fabrication and characterization of nano-Y2O3 dispersed W-Ni-Nb alloys. (February 2018) - Saxena, R.; Patra, A.; Karak, S.K.; Ciupinski, L.
Abstract: The present research work comprises fabrication of nano Y2 O3 (< 50 nm particle size) dispersed W-Ni-Nb alloys with nominal composition of W79 Ni10 Nb10 (Y2 O3 )1 (alloy A), W78 Ni10 Nb10 (Y2 O3 )2 (alloy B) and W72 Ni10 Nb15 (Y2 O3 )3 (alloy C) (all in wt%) by mechanical alloying for 20 h and consolidation by conventional pressureless sintering at 1500 °C for 2 h. The mechanically alloyed powders and consolidated alloys have been characterized by X-ray diffraction, Scanning electron microscopy, Energy dispersive Spectroscopy and Transmission Electron Microscopy. Minimum crystallite size of 20.4 nm has been achieved in alloy C. The formation of NbNi intermetallic phases is evident in the sintered alloys. The bimodality of grains enhances with increases in Y2 O3 addition. Maximum % densification of 93.38% and mean hardness of 5.59 GPa has been recorded in alloy C. The wear depth decreases with increase in Y2 O3 content upto 2 wt%, however further increase results in enhancement of wear depth and wear loss. Preliminary investigation shows that Y2 O3 dispersion upto 1 wt% is effective in providing enhanced oxidation resistance at 900 °C as compared to other alloys. Graphical abstract: Highlights: W-Ni-Nb-Y2 O3 alloys are fabricated by mechanical alloying and conventional liquid phase sintering. Bimodal grain size distribution enhances with increase in Y2 O3 addition. Higher Y2 O3 and Nb containing alloy exhibit improved density and hardness. Increased Y2 O3 dispersion beyond 1 wt% and Nb addition results in poor oxidation resistance.